FUNGSI DINAS SOSIAL DALAM PENDAMPINGAN KORBAN EKSPLOITASI SEKSUAL KOMERSIAL ANAK (ESKA) DI KOTA KENDARI - Adi Saputra, Nur Alam; Arsyad, Muhammad; Sarpin, Sarpin (Universitas Halu Oleo, 2023)
The aim of this research is to identify the factors that cause commercial sexual exploitation of children in the city of Kendari, to identify the role of social services in supporting victims of commercial sexual exploitation of children in the city of Kendari, and to identify barriers in supporting victims to carry out sexual investigations. commercial exploitation. sexual exploitation of children in the city of Kendari. This research is research that uses a qualitative approach with descriptive methods. The data collection techniques used were interview observation and documentation. The results of this study concluded that the social service in assisting victims of child sexual exploitation by carrying out services, empowerment and coaching to victims to carry out handling and planning service policies as well as increasing self-confidence to victims and providing protection and guarantees to victims. And the obstacles of the Social Service in providing assistance or services are the lack of human resources, do not yet have a Women's Social Service Center, and the victim does not want to be open or still does not want to provide information that occurs